UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH KOMBINATORIK SISWA DENGAN MENERAPKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI KELAS XI SMA ISTIQLAL DELITUA - Ammamiarihta Ammamiarihta (AXIOM : Jurnal Pendidikan dan Matematika, 2019)
This study aims to determine the increase in combinatorics problem solving abilities of students after the problem based learning model has been applied. This research was conducted in two cycles. From the results of the initial test obtained a percentage of classical completeness of students' combinatorics problem solving ability of 0% with an average value of 1,24; in the first cycle it increased to 80% with an average of 2,80; and in cycle II it increased to 86,67% with an average of 2,86. Improved student test results are also seen in each combinatorics model. In the distribution model, the average value of students in the cycle I is 3,01 and in the cycle II increases to 3,06. In the partition model, the average value of students in the cycle I is 2,70 and in the cycle II increases to 2,81. In the selection model, the average value of students in the cycle I is 2.68 and in the cycle II increases to 2,70. The management of learning carried out by the teacher in the cycle I was included in the good category, in the cycle II it increased very well. From the results of these studies it can be concluded that the problem based learning model can improve students' combinatorics problem solving abilities.